The Role of Halal Awareness, Halal Certification and Green Product Toward Purchase Intention on Shopee - Andini Rahmadina; Arief Bowo Prayoga Kasmo (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to examine and analyze the influence of halal awareness, halal certification, and green product attributes on purchase intention toward NPURE Acne Face Toner Centella Asiatica on the Shopee platform. The population in this study consists of individuals who use skincare products for acne-prone skin and are familiar with NPURE products in the DKI Jakarta area. The study involved 167 respondents, selected using Hair’s formula for sample size determination. A purposive sampling technique was used to ensure that participants met specific criteria relevant to the research. Data were collected through survey using a questionnaire as the research instrument. The data method applied is the Partial Least Square (PLS). The results show that halal awareness, halal certification, and green product have a positive and significant effect on purchase intention. The implication of this study is to provide relevant insights for PT Penta Natural Kosmetindo and similar enterprises to formulate marketing strategies aligned with consumer preferences in the digital era.